Valuing control over income and time use: A field experiment in Rwanda - Hickman, William; Kramer, Berber; Mollerstrom, Johanna; Seymour, Greg (George Mason University, 2023)
Agricultural development programs often aim to increase women’s incomes and to enhance their control over family resources by offering new work opportunities, but as an unintended negative consequence, these programs may further increase women’s already heavy workloads. By means of a lab-in-the-field experiment in rural Rwanda, we elicit men’s and women’s valuations of control over income, time use, and trade-offs between them. We find that women are willing to sacrifice more household income to increase their control over income than their husbands are. However, the magnitude of respondents’ valuations of control over income is low. On the other hand, both women and men place a high value on time, and this relationship does not vary by gender. Consequently, development programs introducing time-saving practices, technologies, and services may have more positive welfare impacts than programs that primarily increase control over monetary resources.